If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(y) = -1(2x + -3) Reorder the terms: -1y = -1(-3 + 2x) -1y = (-3 * -1 + 2x * -1) -1y = (3 + -2x) Solving -1y = 3 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = -3 + 2x Simplifying y = -3 + 2x
| 7x+3=-3+7x | | 5(y+3)dx=-5xdy | | 13y-7y=-36 | | 1(y)=1(2x+5) | | 4x-2=5(x-5) | | 4+2z-3=9z+8-6z | | 0=-5+n/3 | | 1236478000274773821110183738829202028847374729292974737774939b-777774488849484888848484884444338=65 | | 2x-11x^1/2+15 | | 1=3(x-2)+3-2x | | 12345b-123347=12 | | (w+9)(w-6)=0 | | 10b-34=12 | | e=32/8 | | 4x+5y=180 | | 6=-4+x/2 | | 8z+4z=96 | | 36/f=4 | | 9/4+3y=6y-3/20 | | (x+5)(5x-4)=0 | | k=27/3 | | 12x+14=21 | | 9/4y-3/20+3y=6 | | X+3/4x-3/5=-1/4(x+5/6) | | y=-4(0)-6 | | -4=8+3x | | 5x+4y=180 | | 18+w-13=20 | | 8/3x+1/3x=2x+25/3+8/3x | | -3=-12+x/11 | | 1+3/4v-3/5=-1/4(x+5/6) | | -22-4x=5x+18 |